High Mortality Rate Due to Inflated Prevalence of Drowning Cases; An Observational Study Reflecting Regional Trends and Factors Affecting Asphyxial Deaths Due to Drowning in District Muzaffargarh: Regional Trends and Factors Affecting Asphyxia Deaths Due to Drowning in Muzaffargarh - Sana, Sanaila Gull; Ashraf, Roman; Zehra, Syeda Hina; Murad, Tasneem; Ahmed, Iftikhar; Javed, Sumbul (Pakistan Journal of Health Sciences, 2025)
Asphyxia deaths due to drowning, especially accidental deaths are soaring daily in many areas of Pakistan. This fact led us to conduct this study on prime areas of Muzaffargarh on the bank of River Chenab. Objectives: To determine the frequency of drowning cases and factors affecting their high prevalence. Methods: A retrospective study comprising 5 years (2019-2023), including both genders and age groups, asphyxia deaths particularly due to drowning but excluding unidentified bodies and other modes of asphyxia deaths. All variables are analyzed through SPSS-27. Results: Out of 412 drowning cases, 309 cases belong to accidental drowning (75%) with a predominance of the male population, almost 68.68%. The most prevalent age group involved is 11-20 years (31.31%). The majority of cases happen in the monsoon and summer seasons, 28.88% and 26.45% respectively. Conclusions: It was concluded that asphyxia deaths due to drowning are rising day by day, especially the cases involving accidental deaths. This showed the lack of proper preventive strategies in areas of Chenab River in District Muzaffargarh.